"Red-Yellow-Green": Effect of an Initiative to Guide Surgeon Choice of Orthopaedic Implants. (5th April 2017) - Okike, Kanu; Pollak, Rachael; O'Toole, Robert V.; Pollak, Andrew N.
Abstract : Background: Orthopaedic procedures are expensive, and devices account for a large proportion of the overall costs. Hospitals have employed a variety of strategies to decrease implant costs, but many center on restricting surgeon choice. At our institution, we developed an implant selection tool that guides surgeons toward more cost-effective implants, while minimally restricting choice. The purpose of this study was to assess the effect of this tool on preferred implant usage rates, vendor attitudes toward pricing structure, and hospital implant expenditures. Methods: For 6 commonly used orthopaedic trauma devices, similar constructs were created for the 4 vendors used at our hospital, and the costs were determined. On the basis of these costs, the available options for each device type were categorized as "green" (preferred vendor), "yellow" (midrange), or "red" (used for patient-specific requirements). The "Red-Yellow-Green" chart was posted on the wall of each orthopaedic trauma operating room. To assess the effect of the tool, we compared implant usage patterns before and after implementation of the implant selection tool. We also assessed changes in vendor contract prices, as well as overall savings to our institution. Results: Implant usage changed significantly from 30% "red, " 56% "yellow, " and 14% "green" prior to the intervention, to 9% "red, " 21% "yellow, " and 70% "green" after the intervention (p < 0.0001). As a result of price renegotiation with vendors following implementation, we observed average price decreases that ranged from 1.1% to 22.4%. Average expenditures on these 6 implants decreased 20% during the study period, which represented a savings of 216, 495 per year. Conclusions: At our institution, we designed and implemented "Red-Yellow-Green, " a simple tool that guides surgeons toward the selection of lower-cost implants without violating vendor confidentiality clauses, limiting the implants from which surgeons can choose, or requiring surgeons to discern the prices of complex constructs. Following implementation, hospital implant expenditures decreased as a result of a combination of increased preferred vendor usage by surgeons, as well as increased competition among vendors, which resulted in lower overall prices.